Using He's variational method to seek the traveling wave solution of PHI-four equation - Najafi, Maliheh (International Journal of Applied Mathematical Research, 2012)
In this paper, we established travelling wave solutions of the non-linear equation. The He's variational method was used to construct travelling wave solutions of the PHI-four equation. The obtained results include periodic and solitary wave solutions. It is also shown that the He's variational method, with the help of symbolic computation, provides a powerful mathematical tool for solving other nonlinear evolution equations arising in mathematical physics.